What are the Determinants of Appointing an External Auditor with Forensic Accounting Services? A Cross-Country Study - Shroug Fahd ALmousa; Nafisah Yami; Hashem Alshurafat; Omar Arabiat (Ianna Journal of Interdisciplinary Studies)
Background: This paper presents a cross-country study, including Saudi and Jordan firms, analysing the effect of firm and board characteristics on the decision-making process of appointing an external auditor with forensic accounting services. By understanding the determinants, organisations can make informed decisions about when and how to bring in forensic auditors, thus strengthening their financial integrity, reducing risks, and improving stakeholder confidence.